(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background: The importance of the subject is evidenced by the steadily increasing number of patients with primary-open angle glaucoma (POAG) and absence of a unified theory for the development of POAG. Purpose: To compare the absorption spectra of the aqueous humor (AH) samples from patients with combined cataract and POAG, and those from patients with cataract only, and to identify differences, if any, in parameters of these spectra between the two groups. Materials and Methods: AH samples were obtained from 96 patients (96 eyes including 36 eyes with combined cataract and POAG, and 60 eyes with cataract only), and their absorption spectra were investigated. Results: In the AH samples obtained from patients with combined cataract and POAG or those with cataract only, two absorption peaks were found at 202 nm and 267 nm. The mean optical density at 202 nm of the AH samples obtained from the former patients was higher than that of the samples obtained from the latter patients. The intergroup difference in the optical density at 202 nm (but not at 267 nm) of the AH samples was statistically significant. Conclusion: A statistically significant difference in the optical density of AH samples was found between patients with POAG and those without POAG based on the results of spectroscopy that can be regarded as a valuable adjunct in the diagnosis of patients with this disorder.